Oncologic reconstruction of the proximal humerus with a reverse total shoulder arthroplasty megaprosthesis. Issue 6 (28th August 2018) - Grosel, Timothy W.; Plummer, Darren R.; Mayerson, Joel L.; Scharschmidt, Thomas J.; Barlow, Jonathan D.
Abstract : Background and Purpose: Both malignant and benign tumors of the proximal humerus may necessitate resection of a substantial portion of the proximal humerus, making reconstruction options challenging. While hemiarthroplasty has been a classic treatment, reverse total shoulder replacement may provide better pain relief and function for these patients. Methods: We utilize a two‐surgeon approach for these challenging cases. The orthopedic oncologist resects the tumor. A shoulder‐trained surgeon implants the reverse shoulder replacement. Modern implants, with large glenospheres and modular components, can allow reliable, straightforward reconstructions for these patients. We prefer 6 weeks of postoperative immobilization to decrease the risk of instability. Results: We have completed 13 reverse total shoulder replacements for oncologic shoulder resections, with acceptable clinical outcomes and no complications to date. Conclusion: Reverse total shoulder replacement with long‐stem, modular components can reliably and reproducibly reconstruct the shoulder in patients with oncologic resections of the proximal humerus.